Hak Kepemilikan Tanah (Imamat 25:23-24): Analisis Teologis dan Kontekstualisasi Ketentuan Tahun Yobel di Tengah Konflik Agraria di Indonesia - Sinaga, Hulman (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2025)
AbstractAgrarian conflicts remain a persistent and serious issue in Indonesia. Land, which should serve as a source of livelihood for many, is increasingly controlled by large corporations through state-issued permits. Consequently, indigenous communities that have stewarded the land for generations often face marginalization and even criminalization. This situation raises a fundamental theological question: who truly owns the land—the people, the state, or God? Leviticus 25:23–24 underscores that the land must not be sold permanently, for its ultimate owner is God, while humans are merely sojourners entrusted with its use. This study employs a critical hermeneutical method to interpret the text within its post-exilic context and to contextualize its meaning in relation to contemporary land conflicts in Indonesia, particularly in the Lake Toba region. The findings suggest that the Jubilee principles articulated in Leviticus 25 offer a theological foundation for agrarian reform, affirming that land is a divine gift to be managed with justice, sustainability, and preferential concern for the vulnerable. AbstrakKonflik agraria masih menjadi persoalan serius di Indonesia. Tanah yang seharusnya menjadi sumber kehidupan rakyat justru dikuasai oleh korporasi besar melalui izin pemerintah. Akibatnya masyarakat adat yang telah mengelola tanah secara turun temurun terpinggirkan, bahkan dikriminalisasi. Pertanyaannya, siapa sesungguhnya pemilik tanah—rakyat, negara atau Tuhan? Imamat 25:23-24 menegaskan bahwa tanah tidak boleh dijual permanen karena pemilik sejati adalah Tuhan sedangkan manusia hanyalah pendatang yang diberi hak pakai. Tulisan ini menggunakan analisis hermeneutis teologis untuk menafsirkan teks dalam konteks pasca pembuangan lalu mengkontekstualisasikannya pada konflik tanah di Indonesia, khususnya di kawasan Danau Toba. Hasil kajian menunjukkan bahwa ketentuan Tahun Yobel dalam Imamat 25 dapat menjadi dasar teologis untuk reformasi agraria: tanah adalah titipan Tuhan yang harus dikelola dengan adil, lestari dan berpihak pada kelompok lemah.